Potassium Permanganate-Catalyzed Alpha-Pinene Oxidation: Formation of Coordination Compound with Zinc(II) and Copper(II), and Growth Inhibition Activity on Staphylococcus aureus and Escherichia coli - Masruri Masruri; Rekfa Wika Amini; Mohammad Farid Rahman (Universitas Gadjah Mada, 2016)
Catalytic oxidation of alpha-pinene was investigated using potassium permanganate as an oxidant. The reaction consumed catalyst following stoichiometric amount instead of the catalytic one. The keto-carboxylate compound 2 was afforded as the oxidation product. Further study of its complex compound with copper(II) and zinc(II) was also reported including their activity for inhibiting the growth of Staphylococcus aureus and Escherichia coli. In overall, the complex compound shows important result by inhibiting the bacterial growth.